Making a "Pro": 'Professionalism' after Platforms in Beauty-work - Raval, Noopur; Pal, Joyojeet (CSCW 2019, 2019)
Beauty and Wellness work in India happen largely in the informal sector and are heavily gendered forms of work. The arrival of app-based on-demand platforms that aggregate beauticians and spa therapists to provide at-home services in urban India have aimed to create new efficiencies in this work, providing both the service providers and users of these with new means of transacting. This paper presents findings from an ethnographic study of an app-based platform that provides beauty and wellness services. We interviewed stakeholders including platform company employees, customers, beauty-trainers as well as platform-workers. Our results show the ways in which technology is creating new expectations around professionalism and training, which intersect with the ways workspaces and provider-receiver relationships are articulated around wellness work in urban India. We argue that this case offers an insightful example into the future of work - specifically platform work's attempts to create entrepreneurial subjects, and its tensions with the realities of gender, class and caste as they relate to care labor in India.